The Influence Of Work Motivation And Organizational Culture On Employee Performance Through Job Satisfaction As An Intervening Variable In PT TWC Borobudur, Prambanan, And Ratu Boko (Prambanan Unit) - Arifina, Salma Husna; Setiawati, Trias; Palupi, Majang (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The goal of this research was to examine the relationship between work motivation, organizational culture, and employee performance at PT Taman Wisata Candi Borobudur, Prambanan, and Ratu Boko (Prambanan Unit) by using job satisfaction as a moderator. Specifically, questionnaires were employed to obtain quantitative data for this investigation. A quota sampling technique was used to choose a sample of 38 organic workers to represent the entire population. T-test, F-test, simple linear regression, multiple linear regression, and path analysis are all used to analyze the data collected. The findings revealed a good relationship between work motivation and Job Satisfaction and Employee Performance, as well as a positive relationship between Organizational Culture and Job Satisfaction but a negative relationship between Organizational Culture and Employee Performance. Job satisfaction has been proven to solely operate as a mediator between job motivation and worker productivity. The findings of this study raise intriguing questions for further investigation into the reasons why Organizational Culture in high-performing state-owned enterprises does not positively affect Employee Performance.